2021
DOI: 10.1161/jaha.121.023956
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Delivery of Electrical Shocks and Epinephrine, Guided by Ventricular Fibrillation Amplitude Spectral Area, Reduces Electrical and Adrenergic Myocardial Burden, Improving Survival in Swine

Abstract: Background We previously reported that resuscitation delivering electrical shocks guided by real‐time ventricular fibrillation amplitude spectral area (AMSA) enabled return of spontaneous circulation (ROSC) with fewer shocks, resulting in less myocardial dysfunction. We now hypothesized that AMSA could also guide delivery of epinephrine, expecting further outcome improvement consequent to less electrical and adrenergic burdens. Methods and Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…An excellent paradigm for this is the recent work by Salvatore R. Aiello et al, whose experimental design and protocol were ingenious and clinically meaningful. This comparative study combined a large animal experiment with a clinical guideline-driven resuscitation protocol, and positive results were obtained, although the research topic was focused but not novel (i.e., AMSA) ( 39 ). More importantly, the starting point of this experimental design offers a significant benefit and valuable reference to researchers in this field.…”
Section: Discussionmentioning
confidence: 99%
“…An excellent paradigm for this is the recent work by Salvatore R. Aiello et al, whose experimental design and protocol were ingenious and clinically meaningful. This comparative study combined a large animal experiment with a clinical guideline-driven resuscitation protocol, and positive results were obtained, although the research topic was focused but not novel (i.e., AMSA) ( 39 ). More importantly, the starting point of this experimental design offers a significant benefit and valuable reference to researchers in this field.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge this is the first published investigation about the onset of regional changes in systolic and diastolic biventricular function after transthoracic shocks. Previous imaging investigations have focused on global volumetric changes, while other non-invasive techniques have utilized serology markers 3 , 6 , 22 , 23 . Yet, the electrical pathway from transthoracic shocks can vary across the heart and these global techniques cannot identify the unique distributions of myocardial injury that occur as a result.…”
Section: Discussionmentioning
confidence: 99%
“…However, myocardial injury follows unique pathways through the thorax in each individual and it is unknown how it impacts regional ventricular function. In swine, Aeillo et al demonstrated that increased electrical burden, defined by the cumulative energy of unsuccessful shocks, was linked to reduced LV function and survival 6 . Common functional measures such as ejection fraction (EF) and volumes are limited in that they represent only global ventricular function and the effects of transthoracic shocks on regional myocardial function have yet not been systematically assessed.…”
Section: Introductionmentioning
confidence: 99%
“…The use of AI to automate a more patient-specific approach to resuscitation care using real-time signals such as the ECG is a promising area of investigation. 30,[35][36][37][38] However, clinician adoption of AI to inform medical decisions can be challenged by the "black box" nature of many classification algorithms (eg, deep neural networks). 39,40 This is especially salient for AI applications that might modify guideline care in real time during OHCA resuscitation.…”
Section: Ai and Prediction Of Refractory Vfmentioning
confidence: 99%